Természetjog – házassági jog: Az „erdélyi házasság” fogalma és az erdélyi református és unitárius házassági bíráskodás a 19. században - Nagy, Péter (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
Hungarian marriage law had become complicated by the second half of the 19th century. The different territorial regulations further complicated the coexistence of several denominational laws. This contributed significantly to the spread of marriage migration. The High Court of Marriages of the Calvinist Church in Transylvania reacted to this situation by regulating the ‘per viam instantiae’ proceedings, which became the most controversial legal instrument of the Calvinist marriage law. The Unitarian Church of Transylvania introduced a similar set of rules. It allowed a person or couple who had converted from another denomination to apply for a divorce, provided that the parties could prove their residence in Transylvania. The issue caused tension both within the authorities in Hungary and other Austrian provinces, and even within the Reformed Church in Transylvania.